Muslim Philanthropic Organization, Ecofeminism and Its Contribution to Sustainable Development in Banten, Indonesia - Alawiyyah, Azizah; Nur, Gian Nova Sudrajat; Zainuddin, Fuad (Universitas Gadjah Mada, 2025)
This study explores the role and activities of Lembaga Amil Zakat Harapan Dhuafa (LAZ Harfa) in achieving Sustainable Development Goals (SDGs) in Banten Province through the lens of ecofeminism. This study highlights the importance of women's active participation in sustainable development, using qualitative methods with ethnomethodology and autobiographical approaches. Data were collected through program observations, interviews with LAZ Harfa managers, and autobiographical narratives from empowerment facilitators. The findings show that the dominant top-down approach in SDGs programs by the government often does not integrate the various goals effectively. In contrast, LAZ Harfa's approach, grounded in the principles of ecofeminism, actively involves women in environmental empowerment and management. This approach not only supports gender equality, but also contributes significantly to other sustainable development goals. Local women's knowledge and experience are key to the success of empowerment and sustainable development initiatives in the region.